Kelayakan dan Strategi Pengembangan Usaha Makanan Ringan pada PD Sinar Berlian di Jakarta Barat - Soesetyo Priharjanto; Ma'mun Sarma; Sri Hartoyo (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2012)
The food industry is generally growing with the increase of production capacity is the addition of engine capacity, the addition of human resources caused by the existing production capacity is not sufficient. The purpose of this study were to (1) analyze the feasibility of trading; (2) analyze and evaluate the factors that affect the internal and external business continuity trade; (3) Recommending priorities marketing strategies. The method of collecting the data in this study were collected through observations and interviews. Feasibility study with the financial ratio approach, such as PBP, B/C Ratio, NPV and IRR. The data obtained were analyzed by using the matrix IFE, EFE, IE, SWOT and QSPM. The result of the financial feasibility analysis shows that the PBP for 2.3 years (approximately 27 months), net B/C ratio of more than one (1.75), at a discount rate of 9.2% obtained a value of Rp747.79 millions positive NPV, IRR amounted to 33.60% higher discount rate as required by 9.2%. This indicates that PD snack business. Sinar Berlian financially feasible. Results of identification and evaluation of the factors of strategy, IFE values obtained at 2.776 and 2.677 for the value of EFE. The combination of these two values in the matrix indicates that the marketing strategy lies in the quadrant of the five, namely the growth and stability. The strategies that can be run, ie market penetration, product development and market. Based on calculations derived QSP matrix of the most attractive strategy to be applied is Marketing Aspect which is expanding market share in major Indonesian cities by utilizing the media campaign